Bentuk Code-mixing Bahasa Arab Santri dan Ustaz Pondok Pesantren Darussalam Parmeraan, Kabupaten Padang Lawas Utara: Pendekatan Sosiolinguistik - Ritonga, Arip Rachman; Rahmawati, Dini (Mahira: Journal of Arabic Studies & Teaching, 2025)
The multilingual environment at Pondok Pesantren Darussalam Parmeraan, where santri and ustaz alternate among Arabic, Indonesian, and Batak Mandailing, creates a natural setting for code-mixing in daily communication. This study aims to identify the forms and directions of code-mixing, examine the motivations for its use, and analyze its sociolinguistic functions in both educational and social interactions. A descriptive qualitative approach was employed, with data collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that the dominant forms of code-mixing are insertion, alternation, and congruent lexicalization, occurring outwardly (between Arabic and non-Arabic languages) and inwardly (between Indonesian and Batak Mandailing). Code-mixing functions as a communicative strategy, strengthens group solidarity, and reinforces religious identity within the pesantren community. This study contributes to understanding multilingual communication in Islamic educational settings and provides new insights into tri-lingual code-mixing, a rarely examined phenomenon in Indonesian sociolinguistics.